Application of borehole flow measurements to characterize hydraulic heterogeneities and their impact on the local groundwater flow network - Francani, Vincenzo; Gattinoni, Paola; Schöttler, Marc; Mottini, Sara; Rigamonti, Dario; Vitiello, Mariangela (Italian journal of engineering geology and environment, 2015)
The focus of this study is to examine the use of borehole flow measuring procedures, in order to support conventional methods and information used to characterize heterogeneous aquifers. In general stratigraphic logs, data from pumping tests and piezometric monitoring are used. In this study a combined approach of vertical and horizontal borehole flow measurements and piezometric monitoring is described, to complete and merge available data for the accurate modeling of a complex aquifer. Vertical thermo-flowmeter logs allowed the detection of noticeable heterogeneities: a leaky aquifer, an upward directed leakage and several layers with higher hydraulic conductivity in the lower part of a hydrostratigraphic unit that appeared almost homogeneous. Horizontal in-hole groundwater flow measurements allowed for quantifying the flow in the more productive layers at the bottom of the aquifer, with observed Darcy velocity up to 10-4 m/sin some measuring points. A numerical model was applied to analyze the major differences between a conceptual model of the aquifer obtained by the use of conventional methods of characterization and a model based on the here proposed approach.